Potret Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT ABC Jakarta Barat - Fitria Rahma; Abdul Azis (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The purpose of this study was to determine the portrait of compensation and work discipline on employee performance at PT ABC West Jakarta both partially and simultaneously. The method used in this study is the quantitative method. The population at PT ABC West Jakarta was 86 respondents. The sample used in this study used a saturated sample, which means the same as the population, which was 86 people. The analysis in this study used the SPSS version 25 program. The data analysis method used simple linear regression tests, multiple linear regressions, correlation coefficients, determination coefficients, partial T tests and simultaneous F tests. The results of this study indicate that: There is a significant partial portrait of compensation on employee performance at PT ABC West Jakarta. This can be proven because the compensation variabel (X1) has a T count value of 8.588> T table 1.988 with a significance level of 0.000 <0.05, so H01 is rejected and Ha1 is accepted. There is a significant partial impact of work discipline on employee performance at PT ABC West Jakarta. This can be proven because the work discipline variabel (X2) has a calculated T value of 24.288> T table 1.988 with a significance level of 0.000 <0.05, so H02 is rejected and Ha2 is accepted. There is a significant impact of compensation and work discipline simultaneously on employee performance at PT ABC West Jakarta. This can be proven because the calculated F value of 292.166> F table 3.110 and a significance level of 0.000 <0.05, so H03 is rejected and Ha3 is accepted. The results of the determination coefficient test are shown by the R Square value of 0.876, which means that the compensation variabels (X1) and work discipline (X2) contribute to the employee performance variabel (Y) by 87.6%, while the remaining 12.4% is caused by other variabels not examined in this study.